2021
DOI: 10.1007/s00330-020-07593-z
|View full text |Cite
|
Sign up to set email alerts
|

Normal chest CT in 1091 symptomatic patients with confirmed Covid-19: frequency, characteristics and outcome

Abstract: Objective Frequency of normal chest CT in symptomatic COVID-19 patients as well as the outcome of these patients remains unknown. The objectives of this work were to assess the incidence of initially normal chest CT in a cohort of consecutive confirmed COVID-19 patients with respiratory symptoms and to compare their clinical characteristics and their outcome to matched patients with typical COVID-19 lesions at initial CT. Methods From March 6 th to April 22 nd , all consecutive adult patients referred to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The differences in the frequency of COVID-19 pneumonia on CT observed in the three study groups may explain disease severity differences during hospitalization. In a study that examined clinical outcomes according to presence or absence of pneumonia in symptomatic COVID-19 patients, Leonard-Lorant et al found that the clinical outcomes of COVID-19 patients with an initially pneumonia-negative CT were better than those with a positive finding (25). In addition, several previous studies have reported that patients with extensive pneumonia on CT have a poorer prognosis (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the frequency of COVID-19 pneumonia on CT observed in the three study groups may explain disease severity differences during hospitalization. In a study that examined clinical outcomes according to presence or absence of pneumonia in symptomatic COVID-19 patients, Leonard-Lorant et al found that the clinical outcomes of COVID-19 patients with an initially pneumonia-negative CT were better than those with a positive finding (25). In addition, several previous studies have reported that patients with extensive pneumonia on CT have a poorer prognosis (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Pneumonia is a common cause of hospitalization and death in COVID-19 patients, and computed tomography (CT) images play a vital role in determining the severity and extent of the disease. [8][9][10][11][12] However, the incidence of pneumonia in Omicron itself is low, not all patients can receive immediate CT screening during a pandemic, and it is not necessary to perform CT scans on all Omicron-infected patients. In addition, the CT suites are high-risk areas for hospital-related transmission of COVID-19 and require infection control.…”
Section: Introductionmentioning
confidence: 99%
“…An initial negative chest X-ray or CT does not exclude the diagnosis of SARS-CoV-2 infection, as an infected patient can have a normal imaging test in the early stages of the disease and become positive later. 11 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%